Bioaccumulation of Heavy Metals in Blood and Tissue of Striped Mullet in Two Italian Lakes. Issue 4 (4th November 2014) - Fazio, Francesco; Piccione, Giuseppe; Tribulato, Katia; Ferrantelli, Vincenzo; Giangrosso, Giuseppe; Arfuso, Francesca; Faggio, Caterina
Abstract: Water and sediment from Faro and Ganzirri lakes were tested for cadmium, mercury, and lead. These heavy metals have been assessed in serum and muscles of Striped Mullet Mugil cephalus . A haemogram was performed to find effects of heavy metals on haematological variables. Student's t ‐test showed higher Pb levels in sediments of Ganzirri Lake than Faro Lake. Two‐way analysis of variance showed higher Cd and Pb concentration in muscles samples of Striped Mullet from Ganzirri Lake than from Faro Lake. Significant differences were found among haematological parameters as well. Mullet from Ganzirri Lake had lower white and red blood cell and trombocyte counts and higher mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration than those from Faro Lake. Our results indicate a significant presence of lead in the environmental produces an accumulation of this metal in fish muscles. Received April 2, 2014; accepted June 16, 2014.